PENGARUH PENGGUNAAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP HASIL BELAJAR FISIKA MATERI POKOK BESARAN DAN SATUAN SISWA KELAS X SMA NEGERI 2 PADANGSIDIMPUAN - Siregar, Dedes Asriani (Program Studi Pendidikan Fisika, Institut Pendidikan Tapanuli Selatan, 2023)
The aims of this research is to know whether there is a significant effect between learning model Contextual Teaching and Learning (CTL) to the result of physics in quantity and unit at the class ten students of SMA Negeri 2 Padangsidimpuan. The population is 323 students and sample was taken through cluster sampling, so the sample is 78 students. The data is collected by using questionnaire and test. Then the result of the research is processed in two stages. The first stage by using descriptive analysis, the second stage by using a statistical test correlation “r” product moment and two know whether there is an effect or not is used ttest formula.The result of the analyzed obtained by an average of 2,87 on X varible with the category “good” and Y variable obtained 75,06 with the category is “good”. The score of tcount is bigger then ttable (5,453 > 1,667). It can be concluded that the alternative hypothesis formulated in this research can be accepted the truth.